2017
DOI: 10.1016/j.molcel.2017.05.030
|View full text |Cite
|
Sign up to set email alerts
|

mTORC2 Regulates Amino Acid Metabolism in Cancer by Phosphorylation of the Cystine-Glutamate Antiporter xCT

Abstract: SUMMARY Mutations in cancer reprogram amino acid metabolism to drive tumor growth, but the molecular mechanisms are not well understood. Using an unbiased proteomic screen, we identified mTORC2 as a critical regulator of amino acid metabolism in cancer via phosphorylation of the cystine-glutamate antiporter xCT. mTORC2 phosphorylates serine 26 at the cytosolic N-terminus of xCT, inhibiting its activity. Genetic inhibition of mTORC2, or pharmacologic mTOR kinase inhibition, promotes glutamate secretion, cystine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
147
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 155 publications
(163 citation statements)
references
References 59 publications
8
147
0
Order By: Relevance
“…Of note, post-translational regulation of xCT downstream of PI3K resulting in phosphorylation of Ser 26 and inhibition of Cys 2 uptake has been previously reported (42), and as such is consistent with the results presented here. Gu et al identified mTORC2 but not AKT as the kinase responsible for phosphorylation of xCT at Ser 26 in cells.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Of note, post-translational regulation of xCT downstream of PI3K resulting in phosphorylation of Ser 26 and inhibition of Cys 2 uptake has been previously reported (42), and as such is consistent with the results presented here. Gu et al identified mTORC2 but not AKT as the kinase responsible for phosphorylation of xCT at Ser 26 in cells.…”
Section: Discussionsupporting
confidence: 94%
“…Gu et al identified mTORC2 but not AKT as the kinase responsible for phosphorylation of xCT at Ser 26 in cells. However, consistent with our data, they also showed that AKT can potentially phosphorylate xCT with in vitro kinase assays (42). The motif surrounding Ser 26 in xCT conforms only partially to both the mTOR (43, 44) and the AKT consensus motifs (45, 46), and the responsible kinase in vivo may therefore conceivably depend on distinct cellular contexts.…”
Section: Discussionsupporting
confidence: 91%
“…mTORC2 requires either glucose or acetate for its activated status, and this mTORC2‐dependent glucose sensing mechanism would raise the possibility that under nutrient‐poor conditions, lower mTORC2 signaling could prefer glutamate efflux, cystine uptake, and glutathione synthesis to protect tumor cells from cellular stress at the expense of cell proliferation, the mechanism of which is based on the mTORC2‐dependent regulation of xCT systems (Fig. ) . The findings lead to the proposal that glucose and amino acid metabolism could interact through mTORC2 signaling, which enables cancer cells to promote their survival according to the microenvironment nutrient status …”
Section: Metabolic Reprogramming In Diffuse Gliomasmentioning
confidence: 99%
“…Additionally, combination of an xCT inhibitor, erastin, with Torin1 (dual mTOR kinase inhibitor) resulted in significant synergistic GBM cell death, indicating that increased xCT activity has a major contribution to glutathione synthesis and GBM cell survival upon pharmacological mTOR kinase inhibition (Fig. ) . Furthermore, nuclear factor‐κB‐mediated survival through mutant EGFR‐mTOR signaling could contribute to a novel resistance mechanism of GBM cells to chemotherapy as well as TKI treatment .…”
Section: Molecular Therapies Targeting Mutation‐dependent Metabolismmentioning
confidence: 99%
See 1 more Smart Citation